Kelas Praktis English Public Speaking - Nugraha, Lasmi Septiyanti; Faridah, Faridah; Sabaruddin, Sabaruddin; Atmarani Dewi Purnama (Fakultas Tarbiyah dan Ilmu Keguruan (FTIK) IAIM Sinjai, 2022)
English is a universal language because it is used by most of the countries in the world as the main language. In addition, English is one of the important international languages ​​to be mastered or learned. In terms of education, teaching foreign languages ​​is also a challenge. How to make students understand easily and quickly not to feel bored with the material given. Practical classes are one way to easily teach public speaking. Practical English Public Speaking Class is a method of improving speaking skills in English which is packaged in practical classes in order to create a more pleasant atmosphere. The main objective of this practical class is to increase students' confidence to be able to speak in public with more confidence. In addition, this activity also aims to break the stigma of participants that English is a difficult language to learn. With a fun method and delivery, students will believe that English is an easy and fun subject to learn.